Empathy development from adolescence to adulthood and its consistency across targets - Gaspar, Augusta; Esteves, Francisco (Frontiers in Psychology, 2022)
This research was conducted with two main goals – to contribute to knowledge on the development of empathy from early adolescence to adulthood, including its contribution to decoding emotion expression, and to improve the understanding of the nature of empathy by simultaneously assessing empathy toward two different targets – humans and animals. It unfolded into two studies: One (S1) obtaining measures of empathy toward humans and animals as targets across five age groups (from pre-adolescents to adults); and another (S2) where a subset of the adolescents who participated in S1 were assessed in emotion expression decoding and subjective and physiological responses to emotional video clips. The results of S1 showed that empathy toward animals and most dimensions of empathy toward humans increase toward adulthood, with important gender differences in empathy to animals and humans, and empathy levels in girls starting off in the age trajectory at higher levels, A moderate correlation between empathy toward human and toward animal targets was also found. S2 showed that the expression of positive emotion is better recognized than that of negative emotion, surprise, or neutral expression and that the measure of human-directed empathy predicts successful decoding of negative emotion, whereas skin conductance responses and subjective valence ratings predicted successful identification of positive emotion. Gender differences emerged but not across all age groups nor all subscales. Results yield keys to the developmental “pace” and trajectory of the various dimensions of empathy and to how empathy relates to emotion decoding.